Identifikasi Potensi dan Pengembangan Sistem Pertanian Organik menuju Bali Pulau Organik - Kesumadewi, Anak Agung Istri; Susila, I Wayan; Gunadi, Gusti Alit; Sarjana, Dewa Gede Raka; Diara, I Wayan; Wirya, Gusti Ngurah Alit Susanta (Bali Membangun Bali: Jurnal Bappeda Litbang, 2020)
Purpose: By adopting an agriculture system that is in harmony with nature through an organic farming system approach, it is expected to produce commodities that are healthy and safe for consumption and have a higher economic value so that the two missions can be achieved in the future. Research methods: Research on identifying the potential and development of organic farming systems towards Bali organic islands had been carried out in all regencies and cities in Bali Province on May - December 2019. The research was conducted through a field survey and the results were agreed through FGD with stakeholders. Findings: Development of organic farming systems potentially carried out in almost all districts in Bali except in Klungkung Regency and Denpasar City. Implications: The innovation result of this research is the online, integrated, compact, lightweight, and easy to operate organic database system for Bali Province.